FORM OF LEGAL PROTECTION AGAINST VICTIMS OF PHYSICAL VIOLENCE IN HOUSEHOLD IN THE CONCEPT OF CRIMINAL LAW DECISION ANALYSIS NUMBER 2192/Pid.Sus/2020/PN.Mdn - Meliana Fransisca Sembiring; Rizal Jackson Hutasoit; Rizki (Awang Long Law Review, 2022)
For Indonesian people, household problems are not to be announced, so there are still many Indonesians who are reluctant to report cases of domestic violence (KDRT). People prefer to solve these problems in a familial manner. The creation of PKDRT Law Number 23 in 2004 by the Government did not make domestic violence cases shrink. Data from Komnas Perempuan shows that domestic violence cases during the pandemic increased dramatically, namely there were 319 cases of violence reported, 2/3 of which 213 cases were domestic violence cases, or 19% (2,056 cases) were cases of psychic violence. Therefore, in the future this regulation can be an instrument that can reduce the percentage of crime in the household.